Strengthening Fragile States: Evidence from Mobile Salary Payments in Afghanistan - Joshua E. Blumenstock; Michael Callen; Anastasiia Faikina; Stefano Fiorin; Tarek Ghani; Michael J. Callen (Center for Economic Studies and ifo Institute (CESifo), 2023)
Building state capacity is uniquely challenging in fragile states. We report results from a randomized evaluation of a major Afghan government initiative to increase capacity by modernizing its payroll. The reform, which required teachers to biometrically register and receive salary payments via mobile money, did little to reduce payments to non-existent "ghost" workers, but significantly reduced delays. The reform also improved educational outcomes and increased formal financial inclusion. The impacts were not immediate – highlighting the importance of long time-horizons – and were largest in urban areas. The results have implications for state-building and are potentially actionable for policymakers.
Keywords: D02; D73; C93; 330; mobile money; state-building; corruption